Emotional, mental disorders and depression in adolescents - Azzah Khoridah Maulidiya; Amir Su'udi; Wibowo Wibowo (Jurnal Edukasi Ilmiah Kesehatan, 2024)
Introduction: Adolescence is an essential period in an individual's development characterized by significant physical, emotional, and social changes. Mental, emotional, and depressive disorders are common mental health problems in adolescents and can have a severe impact on their quality of life. This study aims to examine the prevalence, risk factors, symptoms, and strategies for preventing and treating mental and emotional disorders and depression in adolescents. Methods: The design is descriptive and quantitative. Sampling was carried out using a total sampling technique on 68 nursing students. Results: Most of the respondents did not experience mental or emotional disorders, 75%, and did not experience depression, 48.5%, while those who experienced mild depression, 26.5%, moderate depression, 13.2%, and severe depression, 11.8%. Conclusions: It was found that academic pressure, family problems, bullying, and hormonal changes are some of the factors that contribute to the increased risk of mental disorders in adolescents. Symptoms that often appear include profound feelings of sadness, loss of interest or pleasure in daily activities, changes in sleep and eating patterns, and difficulty concentrating. Effective prevention and treatment strategies include mental health education, social support, psychological interventions, and if needed, medical treatment. Parents, educators, and health workers need to work together in early detection and provide appropriate support to reduce the negative impact of mental-emotional disorders and depression on adolescent development.